Experimental evaluation on the effects of energetic additives in the hybrid rocket fuel - Mohamad Anuar, Mai Nurul Fareesya; Sujana, Mohammad Juani; Ismail, Izham Izzat; Azami, Muhammad Hanafi (Penerbit UTM Press, 2024)
This paper evaluates the viability of employing paraffin wax including energetic additives as solid fuel in a hybrid rocket. In this paper, three distinct fuel compositions were used to compare the augmentation of the regression rate. Hybrid rockets combine the best characteristics of solid and liquid rockets, and they provide a multitude of advantages, such as safe handling and storage, a wider variety of fuel, a lower price, and enhanced dependability. However, it has a key drawback that hinders performance: a low regression rate. An earlier study found that doping the fuel with energetic additives such as aluminium, boron, hydrogen, and ammonia might increase the pace of regression. These nanoparticles will enhance evaporation and combustion efficiency, hence accelerating regression. According to the data, using aluminium increases regression rates by up to 21.2%, followed by using magnesium (19.9%), and iron (8.7%), which has the smallest increase in regression rates. According to this study, adding energetic materials to the fuel of hybrid rocket motors has improved the regression rate problem.